Ionizing radiation knowledge amongst medical support staff : a preliminary study / Nor Azwa Yunus ... [et al.] - Yunus, Nor Azwa; Abdullah, Mohd Haris Ridzuan Ooi; Said, Mohamad Aminudin; Pei, Eng Ch’ng (Universiti Teknologi MARA, Pulau Pinang, 2015)
Radiation exposure is one of the critical issues in the medical field. Medical support staff especially those working in nuclear department should possess good knowledge associated with radiation ionization and radiation safety due to a very high chance of being exposed to radiation during radiological procedures. Proper training is of utmost importance in reducing the risk associated with radiation exposure. However, there has been no research conducted as yet to assess the ionizing radiation knowledge amongst Malaysian medical support staff. Often, the impact of job training on increasing radiation safety knowledge is unknown. This study is designed to identify the level of general radiation knowledge and radiation safety knowledge possessed by a group of Malaysian medical support staff; to measure the strength and the direction of the relationship between these two variables; and to assess whether training program can result in a measureable change in the knowledge of medical support staff. A standardized pre-test and post-test questionnaire was administered to each of a group of 27 medical support staff during a training program on radiation safety. The data obtained were analyzed using a descriptive statistics, t-test, and correlation analysis. Based on the findings, it can be observed that the total post-test scores were better than pre-test scores. The findings also revealed that the mean score for radiation safety knowledge was slightly better than the mean score for the general radiation knowledge. There is no significant relationship between the general radiation knowledge and radiation safety knowledge measures. The results of the study indicated that the current knowledge of ionizing radiation among the medical support staff is at moderate level only. It is recommended that a national study be conducted to determine the level of knowledge about radiation among all the medical staff in all Malaysian hospitals. Besides that, future strategies to improve medical support staff’s radiation knowledge also need to be investigated, developed, implemented and evaluated.